Health-economic evaluation of collaborative orthogeriatric care for patients with a hip fracture in Germany: a retrospective cohort study using health and long-term care insurance claims data - Claudia Schulz; Gisela Büchele; Raphael S. Peter; Dietrich Rothenbacher; Christian Brettschneider; Ulrich C. Liener; Clemens Becker; Kilian Rapp; Hans-Helmut König (The European Journal of Health Economics, 2021)
Background: Evidence suggests benefits of orthogeriatric co-management (OGCM) for hip fracture patients. Yet, evidence on cost-effectiveness is limited and based on small datasets. The aim of our study was to conduct an economic evaluation of the German OGCM for geriatric hip fracture patients. Methods This retrospective cohort study was based on German health and long-term care insurance data. Individuals were 80~years and older, sustained a hip fracture in 2014, and were treated in hospitals providing OGCM (OGCM group) or standard care (control group). Health care costs from payer and societal perspective, life years gained (LYG) and cost-effectiveness were investigated within 1~year. We applied weighted gamma and two-part models, and entropy balancing to account for the lack of randomisation. We calculated incremental cost-effectiveness ratios (ICER) and employed the net-benefit approach to construct cost-effectiveness acceptability curves. Results 14,005 patients were treated in OGCM, and 10,512 in standard care hospitals. Total average health care costs per patient were higher in the OGCM group: exteuro1181.53 (p0.167em<0.167em0.001) from payer perspective, and exteuro1408.21 (p0.167em<0.167em0.001) from societal perspective. The ICER equalled exteuro52,378.12/ LYG from payer and exteuro75,703.44/ LYG from societal perspective. The probability for cost-effectiveness would be 95% if the willingness-to-pay was higher than exteuro82,000/ LYG from payer, and exteuro95,000/ LYG from societal perspective. Conclusion Survival improved in hospitals providing OGCM. Costs were found to increase, driven by inpatient and long-term care. The cost-effectiveness depends on the willingness-to-pay. The ICER is likely to improve with a longer follow-up.
Keywords: 610; Orthogeriatric co-management; Economic evaluation; Cost-effectiveness; Entropy balancing